Two new species of Hamacanthidae (Porifera) from the abyssal nodule fields of the Clarion-Clipperton Zone (Pacific Ocean) - Swee-Cheng Lim; Koh-Siang Tan (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Antimicrobial potential of marine sponges and sponge-derived actinomycetes from Mun Nork and Mun Nai Islands, Thailand - Trinset Weeraphan; Chollabuppha Chou; Prapasiri Bunyong; Naphatson Chanthathamrongsiri; Thanchanok Sirirak; Sumaitt Putchakarn; Swee-Cheng Lim; Wongsakorn Phongsopitanun (Regional Studies in Marine Science, 2026)

Diversity and phylogeny of demosponge fauna in the abyssal nodule fields of the eastern Clarion‐Clipperton Zone, Pacific Ocean - Swee‐Cheng Lim; Helena Wiklund; Guadalupe Bribiesca‐Contreras; Adrian G. Glover; Thomas G. Dahlgren; Koh‐Siang Tan (Zoologica Scripta, 2024)
More than 7000 demosponge species have been described to date globally but Plenaster craigi , the most common and abundant species in the eastern CCZ, represents a new family, and possibly in a new order. Interestingly, P. craigi and members of the families Polymastiidae and Hamacanthidae, all filter‐feeding demosponge species, are far more abundant in nodule fields than the carnivorous sponges (Cladorhizidae) which were widely known to be the most dominant demosponge group in the abyssal depths. Lastly, it is highly likely that such tiny demosponges are present in other habitats. They might have been overlooked and/or ignored by sponge researchers in the past due to their tiny size and nondescript habitus. These demosponges could be distinct new species, not juveniles or indeterminates and warrant full taxonomic treatment.

A new species of Macandrewia (Demospongiae, Tetractinellida, Macandrewiidae) from a seamount in the Western Pacific Ocean - Lin Gong; Swee-Cheng Lim; Mei Yang; Xinzheng Li (Journal of Oceanology and Limnology, 2021)

The Biodiversity and Distribution of Abyssal Benthic Foraminifera and Their Possible Ecological Roles: A Synthesis Across the Clarion-Clipperton Zone - Andrew J. Gooday; Franck Lejzerowicz; Aurélie Goineau; Maria Holzmann; Olga Kamenskaya; Hiroshi Kitazato; Swee-Cheng Lim; Jan Pawlowski; Teresa Radziejewska; Zofia Stachowska; Brygida Wawrzyniak-Wydrowska (Frontiers in Marine Science, 2021)
Benthic foraminiferal research in the North Pacific has a long history, with works published over a century ago providing important information about the taxonomy and distribution of morphospecies. These studies focused mainly on areas outside the Clarion-Clipperton Zone (CCZ). Our knowledge of foraminiferal faunas within the CCZ originates largely from recent baseline investigations related to likely future seabed mining of the polymetallic nodule deposits. These have revealed highly diverse assemblages of sediment-dwelling morphospecies among the meiofauna and macrofauna, as well as megafaunal xenophyophores and nodule-attached fauna. Morphological analyses have been complemented by metabarcoding studies that yielded even higher numbers of molecular species (Operational Taxonomic Units - OTUs). Monothalamids, the vast majority undescribed, constitute a substantial proportion of both morphological and molecular datasets, with multichambered agglutinated and calcareous foraminifera being less common. Their importance in this abyssal (>4,000 m depth) habitat likely reflects food limitation combined with carbonate dissolution close to and below the carbonate compensation depth. Literature records, supported in a few cases by genetic data, suggest that many morphospecies found in the CCZ have wide geographical distributions across the Pacific abyss and in other oceans. At smaller spatial scales (several 100s of kilometers) there is a general uniformity in assemblage composition. Nevertheless, many morphospecies are too rare to conclude anything about their geographical distributions. Similarly, the part played by benthic foraminifera in CCZ ecosystems is largely a matter of speculation, although their abundance across different size classes suggests that it is significant. Meiofauna-sized taxa that consume freshly-deposited organic detritus may be important in carbon cycling, particularly at the shallower, more eutrophic eastern end of the CCZ. Megafaunal xenophyophores can provide habitat structure for other organisms, potentially enhancing benthic biodiversity. Foraminifera of all sizes could be among the earliest recolonisers of disturbed or redeposited sediments. Their potential contributions in terms of both ecology and biodiversity make these protists significant members of benthic communities in the CCZ.

Psammobiosis and bioerosion: examining ecological strategies in sponges using the case example Coelocarteria singaporensis - Christine Hanna Lydia Schönberg; Swee-Cheng Lim (Facies, 2019)

A new genus and species of abyssal sponge commonly encrusting polymetallic nodules in the Clarion-Clipperton Zone, East Pacific Ocean - Swee-Cheng Lim; Helena Wiklund; Adrian G. Glover; Thomas G. Dahlgren; Koh-Siang Tan (Systematics and Biodiversity, 2017)